Letter - West Ham Trades Council and Borough Labour Party, 10 May 1926 (West Ham)
1926-05-10 "Letter - West Ham Trades Council and Borough Labour Party, 10 May 1926" [g0248001.jpg], 10 May 1926 Local Organisation